Description of the female of Simulium chayamaritae (Diptera: Simuliidae) from Thailand - Takaoka, Hiroyuki; Srisuka, Wichai; Saeung, Atiporn (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Simulium chayamaritae Takaoka & Srisuka from Thailand belongs to the Simulium darjeelingense species-group of Simulium (Simulium) (Diptera: Simuliidae). The female of this species is described for the first time based on a female reared from a pupa collected from Chiang Mai, Thailand. It is characterized by the sensory vesicle elongate and the inner margins of the arms of the genital fork divergent, then convergent apically. It is similar to the female of S. eshimai Takaoka & Adler of the same species-group from Vietnam. Taxonomic notes are given to separate it from two other species of the S. darjeelingense species-group from India and Malaysia, and 28 of 31 other species of the subgenus Gomphostilbia recorded from Thailand.